From Marginal to Central: The Change in Non-Muslim Citizen Status through Reine Forst's Ethics of Tolerance - Saifi Muiz, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
Indonesia is a country with diverse religions and beliefs, making it vulnerable to horizontal conflicts. Reports from the Setara Institute indicate that religion-based conflicts continue to recur. One of the root causes lies in the conflation of theological and political domains, particularly in the use of the term kafir. As the majority community, Indonesian Muslims often face difficulties in distinguishing the position of this term in religious contexts from that in citizenship. In 2019, Nahdlatul Ulama (NU), through its National Conference (Munas) in Banjar, issued an important decision by replacing the term kafir with non-Muslim in the context of citizenship. This study analyzes that decision using a qualitative approach, focusing on the official documents of the 2019 NU Munas, and examines the stages of this change through the perspective of Reine Forst’s ethics of tolerance. The study offers two main findings. First, the elimination of the term kafir in the civic domain underscores a paradigm shift: the modern state no longer bases the relations among its citizens on religious classification but rather on the principle of equal rights. Second, the NU decision reflects a model of tolerance grounded in respect for humanity rather than purely theological relations. The novelty of this research lies in its attempt to connect the NU Munas decision with Forst’s theory of tolerance, which has rarely been discussed in studies of tolerance in Indonesia. Thus, this study contributes to broadening the understanding of tolerance, not only as a social practice but also as a normative framework that places humanity at the center of respect.